Importancia del trabajador social en el proyecto Rompiendo Barreras de Adultos Mayores con Discapacidad del GAD Machala -2023. - Gutiérres Ocampos, Charles Cristopher; Armijos Romero, Gonzalo Andrés (Machala, 2024)
The intervention of the social worker in the project "Breaking Barriers with Older Adults with Disabilities" in the Decentralized Autonomous Government of Machala is a crucial component for the success and positive impact on the lives of this vulnerable population. The main objective of the project is to promote inclusion and improve the quality of life of older adults with disabilities in the community. The social worker plays a fundamental role in identifying and evaluating the specific needs of each individual. Conducts interviews and social assessments to understand the limitations and challenges faced by older adults with disabilities. This allows us to design personalized interventions adapted to your particular circumstances, coordinate and collaborate closely with other professionals and relevant entities, such as doctors, occupational therapists and community organizations. This multidisciplinary collaboration guarantees comprehensive and holistic care for older adults with disabilities, addressing not only their physical needs, but also their emotional needs, which will develop and facilitate support and training programs for older adults with disabilities. These programs may include workshops on daily living skills, occupational therapy, recreational activities, psychosocial counseling, and family counseling to foster autonomy, independence, and active participation in the community. Promotes community awareness and education about the rights and needs of older adults with disabilities, encourages empathy, respect and acceptance of this vulnerable population, provides emotional and psychological support to both older adults with disabilities and their families. . . Understands the emotional difficulties and psychosocial challenges they may face and provides guidance, advice and support to help them cope and overcome these difficulties.
La intervención de la trabajadora social en el proyecto "Rompiendo Barreras con Adultos Mayores con Discapacidad" en el Gobierno Autónomo Descentralizado de Machala es un componente crucial para el éxito y el impacto positivo en la vida de esta población vulnerable. El proyecto tiene como objetivo principal promover la inclusión y mejorar la calidad de vida de los adultos mayores con discapacidad en la comunidad. La trabajadora social desempeña un papel fundamental en la identificación y evaluación de las necesidades específicas de cada individuo. Realiza entrevistas y evaluaciones sociales para comprender las limitaciones y desafíos que enfrentan los adultos mayores con discapacidad. Esto permite diseñar intervenciones personalizadas y adaptadas a sus circunstancias particulares, coordina y colabora estrechamente con otros profesionales y entidades relevantes, como médicos, terapeutas ocupacionales y organizaciones comunitarias. Esta colaboración multidisciplinaria garantiza una atención integral y holística para los adultos mayores con discapacidad, abordando no solo sus necesidades físicas, sino también emocionales la cual desarrollara y facilitara programas de apoyo y capacitación para los adultos mayores con discapacidad. Estos programas pueden incluir talleres sobre habilidades de vida diaria, terapia ocupacional, actividades recreativas, asesoramiento psicosocial y orientación familiar para fomentar la autonomía, la independencia y la participación activa en la comunidad. Promueve la sensibilización y la educación comunitaria sobre los derechos y las necesidades de los adultos mayores con discapacidad, fomenta la empatía, el respeto y la aceptación de esta población vulnerable, brinda apoyo emocional y psicológico tanto a los adultos mayores con discapacidad como a sus familias. Comprende las dificultades emocionales y los desafíos psicosociales que pueden enfrentar y proporciona orientación, consejería y apoyo para ayudarles a afrontar y superar estas dificultades.
Keywords: ADULTO MAYOR; DISCAPACIDAD; VULNERABLE; TRABAJADORA SOCIAL